Therapy Compliance Level of Chronic Kidney Failure Patients With Hemodialization In The Hemodialization Room - Wahyu Tanoto; Moch. Zaenal B. (Chakra Brahmanda Lentera Institute, 2022)
Background: Chronic kidney failure (CKD) is a functional disorder. Chronic kidney disease is progressive and irreversible. Hemodialysis is a technology for kidney function therapy to remove metabolic wastes or toxins from the body. Compliance is the level of accuracy of a person's behavior. This study aimed to determine the level of adherence to therapy for chronic kidney failure patients with hemodialysis in the hemodialysis room at Mardi Waluyo Hospital, Blitar. Methods: The method used in this research is descriptive. The population in this study was 121 respondents. The research sample was 17 respondents. This study uses a